On-Line Measurement of the Chemical Oxygen Demand in Wastewater in a Pulp and Paper Mill Using Near Infrared Spectroscopy - Dahlbacka, John; Nyström, Josefina; Mossing, Torgny; Geladi, Paul; Lillhonga, Tom (Scientific Research, 2014)
Although near infrared (NIR) spectroscopy has been evaluated for numerous applications, the number of actual on-line or even on-site industrial applications seems to be very limited. In the present paper, the attempts to produce on-line predictions of the chemical oxygen demand (COD) in wastewater from a pulp and paper mill using NIR spectroscopy are described. The task was perceived as very challenging, but with a root mean square error of prediction of 149 mg/l, roughly corresponding to 1/10 of the studied concentration interval, this attempt was deemed as successful. This result was obtained by using partial least squares model regression, interpolated reference values for calibration purposes, and by evenly distributing the calibration data in the concentration space. This work may also represent the first industrial application of on-line COD measurements in wastewater using NIR spectroscopy.
Keywords: Chemical Oxygen Demand (COD); Industrial Wastewater; Near Infrared Spectroscopy (NIR); Multivariate Calibration; On-Line Measurement